2023
DOI: 10.3350/cmh.2022.0336
|View full text |Cite
|
Sign up to set email alerts
|

Screening strategy for non-alcoholic fatty liver disease

Abstract: Nonalcoholic fatty liver disease (NAFLD) is the most common chronic liver disease, affecting approximately 25% of the general population worldwide and is forecasted to increase global health burden in the 21st century. With the advancement of non-invasive tests for assessing and monitoring of steatosis and fibrosis, NAFLD screening is now feasible, and is increasingly highlighted in international guidelines related to Hepatology, Endocrinology and Pediatrics. Identifying high-risk populations (e.g., diabetes m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 141 publications
(230 reference statements)
0
19
0
1
Order By: Relevance
“…Therefore, we defined NAFLD regression with a dual cutoff criterion to take a more conservative approach to determining NAFLD regression using the FLI, which requires a minimum 30-point reduction from the baseline score—for example, the baseline FLI score is 60 or more and the follow-up FLI score is less than 30. Although the FLI has certain limitations in evaluating the presence and absence of NAFLD compared with more rigorous diagnostic methods, such as imaging and liver biopsy, the FLI holds significant clinical implications because it can be easily calculated, even in primary care settings or diabetes clinics lacking imaging equipment (eg, ultrasonography, transient elastography, and magnetic resonance imaging machines) . Third, the present study found through mediation analyses that NAFLD regression should be interpreted with caution because OADs may change BMI, which is used in calculating the FLI .…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Therefore, we defined NAFLD regression with a dual cutoff criterion to take a more conservative approach to determining NAFLD regression using the FLI, which requires a minimum 30-point reduction from the baseline score—for example, the baseline FLI score is 60 or more and the follow-up FLI score is less than 30. Although the FLI has certain limitations in evaluating the presence and absence of NAFLD compared with more rigorous diagnostic methods, such as imaging and liver biopsy, the FLI holds significant clinical implications because it can be easily calculated, even in primary care settings or diabetes clinics lacking imaging equipment (eg, ultrasonography, transient elastography, and magnetic resonance imaging machines) . Third, the present study found through mediation analyses that NAFLD regression should be interpreted with caution because OADs may change BMI, which is used in calculating the FLI .…”
Section: Discussionmentioning
confidence: 73%
“…10 SGLT2 inhibitors were recently introduced and clinical outcomes (eg, HCC) require long-term observation in patients with NAFLD; therefore, we primarily focused on comparing the different classes of OADs for providing benefits such as NAFLD regression using the FLI, a simple and readily available index adopted in numerous studies. We considered composite liver-related outcome as the secondary end point, 1,16 incorporating incidences of liverrelated hospitalization, liver-related mortality, liver transplant, and/or HCC development. Liver-related hospitalization was defined as a case of discharge with the International Statistical Classification of Diseases and Related Health Problems, Tenth Revision (ICD-10) codes corresponding to cirrhosis, decompensated cirrhosis, HCC, other liver diseases, or a case of paracentesis or varix ligation performed during hospitalization.…”
Section: Discussionmentioning
confidence: 99%
“…Overall clinical efficacy was the primary outcome. According to the appropriate guidelines, [26] it was graded into 4 categories: cure, remarkably effective, effective and ineffective, which was calculated according to the ratio of the total number of those who were effectively treated and the total number of people included. The secondary outcomes were the following: liver function indices: AST, ALT; serum lipid indices: TC, TG, HDL-C, LDL-C; BMI; and adverse events.…”
Section: Methodsmentioning
confidence: 99%
“…In their comprehensive review, Zhang and colleagues 11 address this important issue and provide an up-to-date overview of screening strategies for NAFLD.…”
Section: Editorialmentioning
confidence: 99%
“…Zhang et al 11 provide a comprehensive and relevant review for everyday clinical practice. Non-invasive testing strategies using easily available laboratory data for detecting advanced NAFLD disease stages in distinctive risk groups are crucial, since these patients have a high mortality risk and frequently suffer from liver-related complications.…”
Section: Editorialmentioning
confidence: 99%